Perancangan Mebel Multifungsi Untuk Apartemen Tipe Studio - Ricky Risdianto; Andereas Pandu Setiawan (Intra, 2018)
In this time multifunction furniture is one of many furniture that mostly used by people, especially on small places. In studio type apartment that have some narrow space trouble because of too much furniture being used, utilization of multifunction furniture can solve that trouble. The purpose of this designing is to make multifunction furniture that can be use for some user activity and efficient for user circulation (moving space). Designing method that will be used start from interview and survey then do some observation at once in studio type apartment, then do programming that find out problem and solution to solve that problem along with making design concept. Then do some design development, making many alternative sketchs according to concpet that have been made. Design development will end when one design that called final design choosen to make design drawing of that design until enter to the state of making 1:1 protoype. The final result that obtained is multifunction furniture prototype with 1:1 scale that can be used in studio type apartment for real and solve full space because of too much furnitures problem and narrowness of circulation (moving space) of the apartment user.